A new species of Stolephorus (Clupeiformes: Engraulidae) from the Bay of Bengal, India - Gangan, Shardul S; Pavan-Kumar, Annam; Jahageerdar, Shrinivas; Jaiswar, A. K. (Zootaxa, 2020)
A new fish species, Stolephorus tamilensis sp. nov., is described from the East coast of India. The major distinguishing characters are 5–6 small needle-like pre-pelvic scutes on belly; maxilla tip pointed, reaching to border of operculum, concave and indented in the preoperculum; 25–28 gill rakers on lower lobe of the first branchial arch; dorsal fin without spine; 17–19 anal-fin rays. Moreover, S. tamilensis sp. nov. present higher average genetic divergence values at mitochondrial cytochrome c oxidase subunit I and 16S rDNA loci in comparison with congeners. Also, nucleotide diagnostic characters exclusive to S. tamilensis are identified. Neighbor-joining analysis revealed close relation between S. tamilensis  and S. andhraensis.